2016
DOI: 10.1021/acs.jpcb.6b05104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface and Salt Properties on the Ion Distribution around Spherical Nanoparticles: Monte Carlo Simulations

Abstract: Nanoparticle surface charge properties represent key parameters to predict their fate, reactivity, and complexation in natural, biological, and industrial dispersions. In this context, we present here an original approach to better understand the surface charge electrostatic properties of spherical nanoparticles (NPs). The ion distribution around one nanoparticle is investigated using Monte Carlo simulations and by adjusting a wide range of parameters including NP properties (surface charge density and site di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Similar correlation between the surface charge and the valence of the adsorbing counterions was discovered on the basis of electrophoretic measurements performed with colloidal particles 22,25,30,31 including titania. 46 In addition, Monte Carlo calculations were carried out to describe the distribution of multivalent ions around and on charged colloidal particles 56 and planar surfaces. 57 These results and others 58−60 from model calculations also revealed that the strength of the counterion adsorption increases with the valence leading to a decreased effective charge and to charge reversal of the surfaces.…”
Section: ■ Resultssupporting
confidence: 71%
“…Similar correlation between the surface charge and the valence of the adsorbing counterions was discovered on the basis of electrophoretic measurements performed with colloidal particles 22,25,30,31 including titania. 46 In addition, Monte Carlo calculations were carried out to describe the distribution of multivalent ions around and on charged colloidal particles 56 and planar surfaces. 57 These results and others 58−60 from model calculations also revealed that the strength of the counterion adsorption increases with the valence leading to a decreased effective charge and to charge reversal of the surfaces.…”
Section: ■ Resultssupporting
confidence: 71%
“…Key ENM properties that influence colloidal stability include particle size, size distribution, shape, specific surface area, and surface properties (i.e., grafting density of organic ligands, surface charge, and functionality), where the latter material properties predominantly determines whether an ENM is hydrophilic or -phobic (Part et al 2015). It should also be noted that environmental conditions, such as pH, ionic strength, electrolyte concentration, and NOM content significantly influence ENM mobility and transport in (saturated) porous solid matrices, as experimentally reported by several researchers (Akaighe et al 2011;Clavier et al 2016;Ghosh et al 2008;Radniecki et al 2011;Tejamaya et al 2012;Yang et al 2015;Zhou et al 2013). Significant work in the field of ENMs has been conducted evaluating the influence of these ENM and environmental conditions on ENM stability and thus transport in liquid and solid matrices (e.g., Chen and Elimelech 2006;Hotze et al 2010;Li et al 2008;Louie et al 2016;Petosa et al 2010;Phenrat et al 2010;Saleh et al 2010).…”
Section: Influence Of Landfill Leachate Characteristics On Enm Mobilitymentioning
confidence: 75%
“…18 Therefore, effects of particle (or aggregate) properties, possible surface coatings and medium characteristics on particle interactions need to be considered on a more detailed scale. 42 Challenges in predicting α Despite the theoretical basis described above, calculating α ab initio remains very challenging. The extended DLVO theory can be used as a starting point, but it is very difficult to predict α for environmentally relevant scenarios.…”
Section: Attachment Efficiency (α)mentioning
confidence: 99%